2011
DOI: 10.1557/opl.2011.1204
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Nanoimpact Testing of Hard CrAl(Si)N Coatings

Abstract: Statistical studies involving the fracture behavior of coatings can play an important role in the mechanical analysis of films employed in the hard coating industry. In this study, Nanoimpact tests using a cube corner indenter were carried out in various CrAl(Si)N coatings for the quantitative assessment of properties of coatings like non-catastropic failure time and catastrophic failure time. These parameters decrease in value as silicon is incorporated in coatings, showing that this addition results in a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Improved fracture resistance for (Ti,Al)N coatings compared to TiN has been reported in nano-impact tests [75,101]. High Al-fraction (Al = 0.52-0.67) coatings have been developed combining dense nanocrystalline or columnar microstructures, high oxidation resistance, good mechanical properties and low thermal conductivity at elevated temperature with the potential for self-adaptive behaviour through the formation of Al-rich tribo-films [12][13][14][15][16][17][18][19][20][21][22][23]101,[103][104][105][106][107][108][109][110][111][112][113][114][115][116]. These Al-rich coatings typically outperform Ti 0.5 Al 0.5 N in cutting tests and perform well in machining aerospace alloys such as titanium alloys [14,105], Ni-based superalloys (Inconel 718, Waspaloy, ME16) [14,16], and other difficult-to-machine materials including hardened steel [17,[106][107][108], stainless steel [112] and super duplex stainless steel [110].…”
Section: Nitrides On Wc-comentioning
confidence: 99%
See 1 more Smart Citation
“…Improved fracture resistance for (Ti,Al)N coatings compared to TiN has been reported in nano-impact tests [75,101]. High Al-fraction (Al = 0.52-0.67) coatings have been developed combining dense nanocrystalline or columnar microstructures, high oxidation resistance, good mechanical properties and low thermal conductivity at elevated temperature with the potential for self-adaptive behaviour through the formation of Al-rich tribo-films [12][13][14][15][16][17][18][19][20][21][22][23]101,[103][104][105][106][107][108][109][110][111][112][113][114][115][116]. These Al-rich coatings typically outperform Ti 0.5 Al 0.5 N in cutting tests and perform well in machining aerospace alloys such as titanium alloys [14,105], Ni-based superalloys (Inconel 718, Waspaloy, ME16) [14,16], and other difficult-to-machine materials including hardened steel [17,[106][107][108], stainless steel [112] and super duplex stainless steel [110].…”
Section: Nitrides On Wc-comentioning
confidence: 99%
“…Inspektor and Salvador [103] reported that with the increasing Al:Ti ratio, there was a gradual increase in the life of (Ti,Al)N-coated tools when face milling of 4140 steel. The higher Al-fraction coatings display multifunctional and adaptive behaviour in high-speed metal cutting, which results in improved tool life [12][13][14][15][16][17][18][19][20][21][22][23]101,[103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121]. The coatings can more efficiently protect the tool from thermal softening through (i) more effective age-hardening by spinodal decomposition, (ii) lower thermal conductivity and brittleness at elevated temperature, and (iii) protective alumina-based tribo-films.…”
Section: Nitrides On Wc-comentioning
confidence: 99%